Hybrid Ant Colony Optimization Method for the Traveling Salesman Problem - Janjarassuk, Udom (My University, 2024)
The traveling salesman problem (TSP) is a classic problem in computer science and operations research which involves finding the shortest possible route that visits a given set of cities. In this paper, we propose a hybrid algorithm for solving such problem. The algorithm combines the ant colony optimization (ACO) method with the 2-opt heuristic to improve the efficiency for solving the TSP. Instances from the TSPLIB were used to test the algorithm. The results showed that the hybrid ACO algorithm was more effective in solving the TSP as compared to the traditional ACO or the 2-opt heuristic methods.
Keywords: 2-opt heuristic; algorithm; ant colony optimization; hybrid method; optimization; traveling salesman problem